Surface Modification of Monolayer MoS2 by Baking for Biomedical Applications - Wang, Yan; Ma, Yuanjun; Shi, Jinping; Yan, Xiangyu; Luo, Jun; Zhu, Huilong; Jia, Kunpeng; Li, Juan; Zhang, Can Yang (Frontiers in Chemistry, 2020)
Molybdenum disulfide (MoS2), a transition metal dichalcogenide material, possesses great potential in biomedical applications such as chemical/biological sensing, drug/gene delivery, bioimaging, phototherapy, and so on. In particular, monolayer MoS2 has more extensive applications because of its superior physical and chemical properties; for example, it has an ultra-high surface area, is easily modified, and has high biodegradability. It is important to prepare advanced monolayer MoS2 with enhanced energy exchange efficiency (EEE) for the development of MoS2-based nanodevices and therapeutic strategies. In this work, a monolayer MoS2 film was first synthesized through a chemical vapor deposition method, and the surface of MoS2 was further modified via a baking process to develop p-type doping of monolayer MoS2 with high EEE, followed by confirmation by X-ray photoelectron spectroscopy and Raman spectroscopy analysis. The morphology, surface roughness, and layer thickness of monolayer MoS2 before and after baking were thoroughly investigated using atomic force microscopy. The results showed that the surface roughness and layer thickness of monolayer MoS2 modified by baking were obviously increased in comparison with MoS2 without baking, indicating that the surface topography of the monolayer MoS2 film was obviously influenced. Moreover, a photoluminescence spectrum study revealed that p-type doping of monolayer MoS2 displayed much greater photoluminescence ability, which was taken as evidence of higher photothermal conversion efficiency. This study not only developed a novel MoS2 with high EEE for future biomedical applications but also demonstrated that a baking process is a promising way to modify the surface of monolayer MoS2.